A closer look at metaphysic strategies and language achievement of tertiary level Arabic learners - Kamarul Shukri, Mat Teh (2014)
Surveys have shown that there is a significant relationship between the use of Language Learning Strategies (LLS) and the level of language mastery. There are also studies that attempt to explore whether students who are excellent in language use the LLS frequent and a lot. Therefore, this paper describes a study which has been designed to analyze the relationship between the application of metaphysic strategies and the Arabic language level of achievement. The research data was collected by using the self access questionnaire and Arabic language test. The research subjects consist of 385 undergraduate students who are taking an Arabic language course at the Universiti Sultan Zainal Abidin, Terengganu. Descriptive statistics, including Pearson and Independent Sample T-Test were used to analyze the relationship between metaphysic strategies used and the level of Arabic language achievement. The findings from this study were:1) there was a significant correlation between metaphysic strategies used and the language achievement.2) there were significant differences in metaphysic strategies used based on the level of Arabic language achievement.3) Overall, good language learners possess a richer repertoire of strategies and employ metaphysic strategies more frequently than did their counterparts in lower achievement level categories.